Estágio Profissional: Da formação à profissão uma reflexão sobre o processo de avaliação como meio de aprendizagem - Maria Inês Soares Pinto Alves (2024)
This report presents a comprehensive overview of my experience during the School Placement in Physical Education. Throughout this document, various as-pects of the School Placement are addressed, from lesson planning and execu-tion to student assessment and professional development. I will also explore ex-tracurricular activities and events that contributed to my growth as a teacher. Dur-ing the School Placement, I was challenged to grow and refine my skills. I ex-plored different pedagogical models, such as the Direct Instruction Model, the Sports Education Model, and the Cooperative Learning Model, understanding the successes and failures of each. Assessment played a fundamental role in my experience, from diagnostic assessments that allowed me to adapt my teaching to students' needs to continuous assessment, which balanced recognition of stu-dents' efforts. Furthermore, the discovery of goal-based assessment became a subject of study. During the School Placement, I actively participated in organiz-ing extracurricular activities that enriched students' experiences and allowed me to grow as a teacher. I realized that being a teacher is more than imparting knowledge; it involves being a leader, a mediator, an activity designer, and, above all, an advocate for the importance of Physical Education. This journey led me to question my own professional identity and recognize the importance of continu-ous reflection in my teaching practice. In summary, this internship experience transformed me into a more conscientious teacher. I carry with me the lessons learned and the valuable memories of these significant moments. This journey not only shaped my view of the Physical Education profession but also my own professional identity, and I look forward to continuing to grow and contribute to the education of my students.